PENDIDIKAN KEUANGAN UNTUK MENINGKATKAN LITERASI KEUANGAN MELALUI METODE STORY TELLING PADA ANAK USIA SEKOLAH - Anwar, Syamsul; Yuangga, Kharisma Danang; Hamda, Nasmal; Jaya, Fitra; Nurhasanah, Enok (Abdi Laksana : Jurnal Pengabdian Kepada Masyarakat, 2020)
Community service is carried out in the neighborhood of the community around the 1001 Buku Community at Jl. Kemuning 3. Utan Kayu Utara Matraman, East Jakarta, found by school-age children saving, saving prefers something that becomes a habit. Various research results need to be instilled the values of saving habits are needed. Implanting financial literacy values as early as possible will be needed for understanding and knowledge about financial literacy and also the level of welfare in the future. The cognitive properties of children are very effective for instilling financial literacy values. The family which is the first community is a place that manages financial literacy values very effectively. The role that is still concrete and still in school development is also very important in order to provide knowledge about financial literacy education to children. Joint commitment and synergy of all parties that are needed to succeed the values of financial literacy through the family or school. The ability of financial management is also needed to prepare human needs in the future. To meet the needs of daily needs, the need for health, educational needs of children and the need for old age insurance is needed for financial management that is issued and planned.